Bearing damage analysis / Md. Asmawi Said and Wan Sadeli Wan Ismail - Said, Md. Asmawi; Wan Ismail, Wan Sadeli (Faculty of Mechanical Engineering, 2001)
Different types of bearings, materials used in bearings, Lubrication and Inspection of bearings are presented in this report. Bearing failures and their causes are dealt in detail Different types of Bearing damages are illustrated with suitable figures. Roughness and Roundness tests were conducted and the results are presented. The differences in the surface roughness and roundness were found by comparing new and old bearings. The procedure for conducting Multi-element Oil Analyzer (MOA) is presented along with a sample test result. This work gives an exposure to bearing wear, a few techniques for analyzing worn bearings and also oil analysis procedure.